Eksplorasi Ragam Strategi Pemasaran pada Biro Haji dan Umrah: dalam Meningkatkan Daya Saing Layanan pada biro haji dan umrah pada PT lintas persada - Fitria Agustin Widyastuti; Jauharotina Alfadhilah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the marketing strategies implemented by PT Prayogi Lintas Persada Tours and Travel to enhance the competitiveness of its Hajj and Umrah services amidst increasingly fierce competition among pilgrimage travel agencies. Companies are required to develop innovative marketing strategies that are oriented toward pilgrims' needs in order to maintain their existence and maintain public trust. This study uses a qualitative descriptive approach with a literature review method through a review of various relevant sources. The results show that PT Prayogi Lintas Persada Tours and Travel implements various marketing strategies, such as service marketing, utilizing social media for digital marketing, educational seminars, home sharing activities, direct sales, holding annual events, and offering affordable Umrah programs with special prices. These strategies focus not only on product promotion but also on building pilgrim trust, improving service quality, and fostering long-term relationships with customers. Furthermore, improving the quality of human resources and pilgrim experience are crucial factors in strengthening pilgrim loyalty and enhancing the company's image. This study concludes that the combination of digital marketing, relationship-based services, and improving service quality can sustainably strengthen the competitiveness of pilgrim travel agencies. Therefore, companies need to continue to develop creative marketing strategies that focus on the needs of pilgrims to remain competitive in the Hajj and Umrah travel services sector.